Use the Rules of Boolean Algebra to show that

Discussion in 'Homework Help' started by kiwiasker, Mar 28, 2010.

  1. kiwiasker

    Thread Starter New Member

    Mar 28, 2010
    5
    0
    Use the rules of Boolean Algebra to show that

    [B+A(C+D)]' = A'B' + B'C'D'

    Thanks, could you also step me through it as am having difficulty working these ones out, i get very close but i seem to simplify it too far.
     
  2. kiwiasker

    Thread Starter New Member

    Mar 28, 2010
    5
    0
    I did the following

    B' + A'(C'+D')
    B" + A'C' + A'D'
    B'+ A'(C'+D')

    but cannot work out how to make this equal the answer.

    Thanks
     
  3. sickkid

    New Member

    Mar 27, 2010
    4
    0
    use DeMogan's

    =B' (AC)' (AD)' DeMogan's
    =B'{(A'+C')(A'+D')}DeMogan'
    =B'(A'+C'D')
    =A'B'+A'C'D'
     
  4. sickkid

    New Member

    Mar 27, 2010
    4
    0
    use DeMogan's

    =B' (AC)' (AD)' DeMogan's
    =B'{(A'+C')(A'+D')}DeMogan'
    =B'(A'+C'D')
    =A'B'+A'C'D'
     
Loading...